2011
DOI: 10.1149/1.3570221
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SO2 on the Long-Term Durability of SOFC Cathodes

Abstract: Sulfur poisoning effect on the electrochemical performance and long-term durability of SOFC cathodes has been investigated for (La 0.8 Sr 0.2 ) 0.98 MnO 3 (LSM) and La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 (LSCF) up to 1000 hours. Gradual degradation of performance occurred, associated with the formation of strontium sulfate, which depended on SO 2 concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…These perovskites easily form carbonates and sulphates (mainly Ba and Sr carbonates/sulphates) or undergo phase segregation [13,16]. This was also observed in several works focused on La0.6Sr0.4Co0.2Fe0.8O3-δ stability when used as SOFC cathodes exposed to CO2 and SO2 [28][29][30], as well as for similar perovskites consisting of La0.6Sr0.4CoO3-δ [31,32]. In addition, the presence of steam in the system affects both the oxygen transport properties and the thermochemical resistance of MIECs [15,[33][34][35].…”
Section: So2supporting
confidence: 61%
“…These perovskites easily form carbonates and sulphates (mainly Ba and Sr carbonates/sulphates) or undergo phase segregation [13,16]. This was also observed in several works focused on La0.6Sr0.4Co0.2Fe0.8O3-δ stability when used as SOFC cathodes exposed to CO2 and SO2 [28][29][30], as well as for similar perovskites consisting of La0.6Sr0.4CoO3-δ [31,32]. In addition, the presence of steam in the system affects both the oxygen transport properties and the thermochemical resistance of MIECs [15,[33][34][35].…”
Section: So2supporting
confidence: 61%
“…Various volatile impurities exist in SOC stacks, such as gaseous CrO 3 from chromia-forming metallic interconnects and high-temperature alloys used in Balance-of-Plant (BoP) components, SO 2 , CO 2 and H 2 O from airstream and boron species from borosilicate glass sealants. Surface-segregated cations tend to interact actively with these volatile impurities, leading to the deposition of impurities, microstructural changes and operating instability [39,48,49,57,[187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203].…”
Section: Reactivity Of Segregated Cation Species With Volatile Impuritiesmentioning
confidence: 99%
“…Sulphur in air streams can significantly affect the performance and durability of SOFCs [191,215,216]. For example, Wang et al [217] studied the mechanism and kinetics of sulphur deposition on LSM electrodes at 700 °C and 800 °C in 1 ppm and 10 ppm SO 2 and reported that the deposition of SO Xiong et al [191] also investigated the sulphur poisoning of LSM electrodes in highly concentrated 0.01% SO 2 in air and reported that the LSM electrode was relatively stable during cathodic polarization at 800 °C for 5 h. On the other hand, Liu et al [190] tested a double-layer oxygen electrode with an LSM-ScSZ inner layer and an LSM outer layer in 20 ppm SO 2 and reported that after cathodic polarization at 800 °C for 1000 h, SrSO 4 particles were observed around the LSM particles in both layers of the electrode. Wang et al [218] further reported that the deposition of sulphur and formation of SrSO 4 were at the LSM/YSZ interface in the presence of 1 ppm SO 2 at 800 °C under anodic polarization conditions and attributed this to the fact that anodic polarization can promote SrO segregation at the LSM close to the YSZ electrolyte, promoting the formation of SrSO 4 and interfacial delamination.…”
Section: Somentioning
confidence: 99%
See 1 more Smart Citation
“…45 The results are in good accordance with the previous experimental results, i.e., the sulfur poisoning deactivates the active cathode and causes deterioration in the microstructure. 9,10,13,20 It also offers a deep understanding of SO 2 poisoning of the LSM cathode and helps to optimize the material composition and morphology to avoid potential mechanical failure and catalytic deactivation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%